ANALYSIS OF FACTORS AFFECTING EMPLOYEE PERFORMANCE AT PIZZA HUT DELIVERY WITH EMPLOYEE INVOLVEMENT AS A MEDIATING VARIABLE - Evi Silvana Muchsinati; Murni Murni (Journal of Global Business and Management Review, 2023)
Pizza Hut Delivery is a fast food restaurant that innovates by ordering special takeout and delivery. The purpose of this study is to analyze the factors that affect employee performance at Pizza Hut Delivery in Batam City with employee involvement as a mediation variable. The sampling of this study used a saturated sampling method by distributing questionnaires to 55 employees of Pizza Hut Delivery in Batam City. Tests were conducted using Smart PLS. The results in the study stated that training and development variables on employee performance with employee involvement as a mediating variable had a positive insignificant effect, compensation and benefits and organizational fairness on employee performance with employee involvement as mediation had a significant positive effect.